Transovarial Transmission Index of Dengue Virus on Aedes aegypti and Aedes albopictus Mosquitoes in Malalayang District in Manado, North Sulawesi, Indonesia - Angle Maria Hesti Sorisi; Sitti Rahmah Umniyati; Tri Baskoro Tunggul Satoto (Pusat Kedokteran Tropis, 2011)
Introduction: Dengue Hemorrhagic Fever (DHF) is an infectious vector-borne disease caused by Aedes sp mosquitoes still cause serious health problem in Indonesia. Based on Manado Health Office Report, Malalayang was identified as dengue-endemic areas. In 2010, number of DHF cases in Malalayang is 211 cases with Incidence Rate (IR) 328 per 100,000 populations. Dengue viruses (DENV) survive in nature by two mechanisms; by horizontal transmission through infected vertebrates and mosquitoes, and by vertical (transovarial) transmission in the mosquitoes. Transovarial transmission is assumed as an important aspect in the maintanance of DENV during inter epidemic, but this problem has not been studied in Malalayang District, Manado. An effort to prevent and control DHF requires knowledge of an Aedes sp Dengue virus transovarial infection.Objectives: To prove the existence of Dengue virus transmission in Ae. aegypti and Ae. albopictus mosquitoes and its relationship with the incidence of DHF in Malalayang District in Manado, North Sulawesi, Indonesia.Methods: The method of this research was an observational analytic study with cross-sectional design. Study samples were unbloodfed Aedes aegypti and Aedes albopictus mosquitoes on the F1 generation from ovitrap placed in five selected villages based on the number of cases in the District Malalayang. The secondary data of DHF patients from Malalayang district was obtained from Health Office Manado and the Community Health Center in 2010. The presence of dengue antigen in head squashes preparation were detected using monoclonal antibody against dengue (DSSE10) based on immunohistochemical streptavidin biotin peroxidase complex (ISBPC) technique to confirm the presence of transovarial transmission of dengue virus both in Ae. Aegypti and Ae. Albopictus, and to obtain the data of transovarial transmission index. Fisher’s Exact test and Pearson correlation are used to analyze those data.Results: Transovarial transmission of Dengue virus in Aedes sp was found from 5 villages in Malalayang district with Transovarial Transmission Index (TTI) ranges 6.1%-17.1%. Statistic test showed significant differences in positive rate (p-value=0.00<0.05) on Ae. aegypti higher than Ae. albopictus. It is also known that there is no statistically significant correlation (p-value=0.528>0.05) between the Aedes sp. Dengue virus TTI and DHF IR in Malalayang district.Conclusion: This study demonstrates the existence of Dengue virus transovarial transmission in Aedes sp in Malalayang district. Ae. aegypti’s TTI is higher than that of Ae. Albopictus, and no significant correlation between TTI and DHF IR in Malalayang district.Keywords: DHF, transovarial transmission, Ae. aegypti, Ae. albopictus